Vegetation profile around the hornbill nest tree (Bucerotidae) at Way Rilau Research Station, Forest Management Unit (FMU) Batutegi - Elza Febrina Aulia; Dian Iswandaru; Robithotul Huda; Aris Hidayat; Aris Subagio (Global Forest Journal., 2026)
Hornbills are birds capable of flying over long distances, ranging approximately from 39 to 55 km. However, habitat loss caused by widespread forest encroachment poses a serious threat to their survival. Modeling to visualize the canopy structure of potential trees can help visualize the stand profile at the Way Rilau Research Station. The aim is to analyze the characteristics of potential hornbill nests in habitats identified as suitable for these birds. The research was conducted from December 2024 to January 2025 at the Way Rilau Research Station (SRWR), FMU Batutegi, Tanggamus Regency. Data collection uses vegetation analysis, including observations, to identify trees within a 20 m x 20 m plot. The data is analyzed using the Spatially Explicit Individual-based Forest Simulator (SExI-FS) software to model and project canopy profiles digitally and analyze dominance across all plots using the Important Value Index (IVI). The vegetation analysis identified 14 families and 24 tree species, including potential nesting trees such as Kepak, Lengsar, Pasang Merah, and Sempur. The highest Importance Value Index in this analysis was Quercus sundaicus (40.96%), followed by Dipterocarpus korthalsii (32.74%) and Corypha utan (25.03%). These results were projected as a stand profile using SExI-FS software to visualize the conditions around potential nest trees and the criteria. Based on these projections, the potential nest trees have larger crowns than the surrounding supporting trees